Intertextuality, subjectivity, and meaning in Liszt’s Deux Polonaises - Cormac, Joanne (Oxford University Press, 2019)
This article brings the concepts of intertextuality and subjectivity into dialogue in order to advance our understanding of both and to generate new readings of two pieces that are rich in intertextual relationships and also raise complex questions about subjectivity: Liszt’s Deux Polonaises. I argue that, not only are intertextuality and subjectivity codependent, intertextuality also influences the way subjectivities behave and their characteristics. Furthermore, the performer has a fundamental influence on how subjectivities are expressed, challenging our understanding of who retains authorial control. The Deux Polonaises are also related to a literary intertext: Liszt’s F. Chopin, written in the wake of Chopin’s death. This book offers fascinating insight into the potential meanings behind the intertextual references and the play of subjectivities within the pieces, and connects the Deux Polonaises to the emotive historical and political context of their composition. It opens up multiple meanings that are related to contemporary conceptions of the polonaise, and the symbols of Polish cultural Romanticism with which the genre was intertwined.